Fashion in popular culture literature, media and contemporary studies - Hancock, Joseph; Johnson-Woods, Toni; Karaminas, Vicki (Bristol Intellect, 2013)
Combines fashion theory with approaches from literature, art, advertising, music, media studies, material studies, and sociology to consider the function of fashion within popular culture in Europe, Australia, and the United States.
Brand this way : Lady Gaga's fashion as storytelling context to the GLBT community Joseph H. Hancock, II -- Navigating cultural anxiety : strategic ambiguity in Lisbeth Salander's style-fashion-dress Susan B. Kaiser -- Australian gothic : Black light angels, appearance, and subcultural style Vicki Karaminas -- Fashionable addiction : the path to heroic chic Alphonso D. McClendon -- Dames and design : fashion and appearance on pulp fiction covers, 1950-1960 Toni Johnson-Woods -- Territories of knowledge and nostalgia in modern fashion designer life writing Ilya Parkins -- Looking for Mr. Benson : the black leather motorcycle jacket and narratives of masculinities Marvin J. Taylor -- Fashion photography, phallocentrism, and feminist critique Louise Wallenbert -- "He can't love me if I'm ugly": the recurring theme of popular beauty in the television soap opera Days of our lives Andrew Reilly and Nancy A. Rudd -- Redressing the devil's wardrobe : representing and re-reading the darker side of fashion in chick lit novels Anne Peirsono-Smith -- Redeeming the voices of reform Patricia A. Cunningham -- The language of luxury in eighteenth-century France Paula von Wachenfeldt -- The devil of fashion : women, fashion, and the nation in early-twentieth-century German and Swedish cultural magazines Andrea Kollnitz -- Rome : eternal city of fashion and film Eugenia Paulicelli.
"Drexel University, Antoinette Wesphal College of Media Arts & Design"--Title page verso.
Includes bibliographical references and index.
Keywords: Clothing and dress -- Social aspects; Fashion; Fashion in literature; Clothing and dress in literature; Popular culture